Tooth Profile Modification and Experimental Study of Double Circular Arc Flexsplines in Harmonic Reducers - Huang Bing; Lou Junqiang; Cen Guojian; Luo Limin; Li Guoping (Jixie chuandong)
Aiming at the problem of gear interference in the meshing transmission process of the double circular arc flexspline of the harmonic reducer in the actual working condition, based on the finite element method of tooth surface contact analysis between the flexspline and the circular spline, the flexspline tooth is modified by a two-stage helix modification method, and then the comprehensive performance of the prototype is tested. The results show that the maximum contact stress of the modified flexspline to the tooth surface of the circular spline is 72 MPa, which is 368 MPa less than that before the modification, and the contact stress of the other positions of the modified flexspline is slightly higher than that before the modification, which not only effectively avoids the problem of gear interference, but also improves the meshing transmission performance of the harmonic reducer. The comparative test of the prototype also verifies that the transmission performance of the harmonic reducer after the modification of the flexspline is better than that before the modification. This work is useful for the analysis on the dynamic transmission characteristics of the harmonic reducer.